Ethnolinguistic Chicago : language and literacy in the city's neighborhoods - Farr, Marcia (Lawrence Erlbaum Associates, 2004)
Often cited as a quintessential American city, Chicago is and always has been a city of immigrants, and is one of the most linguistically diverse cities in the United States. Language is central to social identity, this work look at the related issues of language and ethnicity.